2019
DOI: 10.3390/ani9080497
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Zinc and Fibre Source can Influence the Mineral and Antioxidant Status of Piglets

Abstract: The study investigated the effect of dietary zinc glycine chelate and potato fibre on the absorption and utilisation of Zn, Cu, Fe, and Mn; the activity of Zn-containing enzymes (superoxide dismutase, SOD; alkaline phosphatase, ALP); and zinc transporter concentrations (metalothionein1, MT1; zinc transporter1, ZnT1) in tissues, with a special emphasis on the small intestine. Twenty-four barrows (Danbred × Duroc) were randomly allotted to four diets (supplemented with 10 g/kg of crude fibre and 120 mg Zn/kg) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…It also helps in the development of the gastrointestinal tract in pigs, preventing diarrhea, and thus affecting growth [ 17 ]. The natural zinc content of feedstuff is insufficient for pigs, and zinc is usually added in an inorganic form, such as ZnO or ZnSO 4 [ 35 ]. The ZnO form has low reactivity and bioavailability, and the ZnSO 4 form is hygroscopic and reacts with rapid ions to form free radicals to accelerate the breakdown of fatty acids, vitamins, and other nutrients in the feed [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also helps in the development of the gastrointestinal tract in pigs, preventing diarrhea, and thus affecting growth [ 17 ]. The natural zinc content of feedstuff is insufficient for pigs, and zinc is usually added in an inorganic form, such as ZnO or ZnSO 4 [ 35 ]. The ZnO form has low reactivity and bioavailability, and the ZnSO 4 form is hygroscopic and reacts with rapid ions to form free radicals to accelerate the breakdown of fatty acids, vitamins, and other nutrients in the feed [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZnProt supplementation reduced plasma and hepatic Cu concentrations, which could indicate sequestration of dietary Cu in intestinal MT induced by feeding with the ZnProt diet. Low intracellular available Cu bound to MT could affect Fe and Mn transport through the Cu-dependent protein hephaestin and a common transporter, ferroportin [56,57]. Unfortunately, we did not measure MT concentrations in the intestine mucosa, so our results cannot clearly indicate binding of Cu to MT.…”
Section: Discussionmentioning
confidence: 87%
“…Liu et al [ 116 ] reported that combinations of Zn oxide and tannins (ZnO + hydrolysable tannins) improved the antioxidant capacity and digestive enzymes of pigs. Organic zinc (Zn glycinate and Zn methionine) also influences the pigs’ antioxidant status and helps maintain a healthy immune system [ 117 , 118 ]. In another study, supplementation of Se and vitamin E at high levels attenuated HS’s impact on the intestinal barrier integrity of pigs, associated with a depletion of OS, as assessed by decrease in antioxidant enzymes [ 119 ].…”
Section: Mitigation Of Heat-stress-induced Intestinal Permeability By Antioxidantsmentioning
confidence: 99%